Purification and properties of NADP-dependent glutamate dehydrogenase from Ruminococcus flavefaciens FD-1. - Duncan, P A (1992)
Glutamate dehydrogenase (GDH) (L-glutamate:NADP+ oxidoreductase, deaminating, EC 1.4.1.4) from the cellulolytic ruminal bacterium Ruminococcus flavefaciens has been purified and characterized. The native enzyme and subunit are 280 and 48 kDa, respectively, suggesting that the native enzyme is a hexamer. The enzyme requires 0.5 M KCl for optimal activity and has a pH optimum of 6.9 to 7.0. The Kms for ammonia, alpha-ketoglutarate, and glutamate are 19, 0.41, and 62 mM, respectively. The sigmoidal NADPH saturation curve revealed positive cooperativity for the binding of this coenzyme. The first residue in the N-terminal amino acid sequence from R. flavefaciens GDH was alanine, suggesting that the protein may be modified posttranslationally. Comparison of the N-terminal sequence with those of Escherichia coli, Salmonella typhimurium, and Clostridium symbiosum revealed only 39% amino acid homologies. The GDH from R. flavefaciens was unique in that its specific activity was highest during ammonia-limited growth but was not affected by ammonia shock treatment (20 mM).